2012
DOI: 10.1590/s1413-81232012001000029
|View full text |Cite
|
Sign up to set email alerts
|

Da vigilância para prevenção de acidentes de trabalho: contribuição da ergonomia da atividade

Abstract: Da vigilância para prevenção de acidentes de trabalho: contribuição da ergonomia da atividadeFrom surveillance to work-related accident prevention: the contribution of the ergonomics of the activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
29

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 9 publications
3
12
0
29
Order By: Relevance
“…Out of the total number of workers, 67.9% (ANL NR: ANL WR: AWL) were injured when employed for than 36 months, and 47.3% of accidents with leave -the largest proportion -occurred when the workers were employed for 12 months or less. This is consistent with the finding of Vilela et al (2012), who also found that the highest rates of accidents requiring leave happened within the first 12 months of employment, and recorded that the workers complained not having received proper training to safely carry out their activities, such as on the use of knives for carcass cut-up. Most accidents happen with less experienced workers (Araujo, 2008;Vilela et al, 2012).…”
Section: Indicators Of Work Accidents In Slaughter Refrigerators and supporting
confidence: 90%
See 3 more Smart Citations
“…Out of the total number of workers, 67.9% (ANL NR: ANL WR: AWL) were injured when employed for than 36 months, and 47.3% of accidents with leave -the largest proportion -occurred when the workers were employed for 12 months or less. This is consistent with the finding of Vilela et al (2012), who also found that the highest rates of accidents requiring leave happened within the first 12 months of employment, and recorded that the workers complained not having received proper training to safely carry out their activities, such as on the use of knives for carcass cut-up. Most accidents happen with less experienced workers (Araujo, 2008;Vilela et al, 2012).…”
Section: Indicators Of Work Accidents In Slaughter Refrigerators and supporting
confidence: 90%
“…This is consistent with the finding of Vilela et al (2012), who also found that the highest rates of accidents requiring leave happened within the first 12 months of employment, and recorded that the workers complained not having received proper training to safely carry out their activities, such as on the use of knives for carcass cut-up. Most accidents happen with less experienced workers (Araujo, 2008;Vilela et al, 2012). Studies in slaughterhouses in the USA indicate that workers receive little training and are often forced to work under the threat of dismissal if they refuse to work (Harmse et al, 2016;Human Rights Watch, 2004;Lipscomb et al, 2007).…”
Section: Indicators Of Work Accidents In Slaughter Refrigerators and supporting
confidence: 90%
See 2 more Smart Citations
“…Na literatura, a dor osteomuscular tem sido abordada como uma das principais causas de absenteísmo e redução de produtividade no trabalho. 9,14,23 Produz incapacidade física e funcional, causa o absenteísmo e comprometimento laboral, gerando aumento dos custos para os sistemas de saúde. 24,25 Como limitações do estudo citam-se: o delineamento transversal, no qual não se pode inferir causalidade (viés da…”
Section: Agr Adecimentosunclassified